PENGARUH KEGIATAN EKSTRAKURIKULER OLAHRAGA TERHADAP KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR GUGUS II KASIHAN BANTUL - Adelbertus Chun Chun; Bahtiyar Heru Susanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of sports extracurricular activities on the social skills of elementary school students in Cluster II Kasihan, Bantul. The research employed a quantitative approach with a correlational design. The population consisted of all elementary school students in Cluster II Kasihan Bantul, with a sample of 110 students selected using purposive sampling, specifically students who participated in sports extracurricular activities. Data were collected through closed-ended questionnaires using a four-point Likert scale and analyzed using Pearson correlation and simple linear regression. The results showed a Pearson correlation coefficient of 0.743 with a significance value of 0.000 (p < 0.05), indicating a strong and positive relationship between sports extracurricular activities and students’ social skills. Furthermore, the regression analysis revealed an R Square value of 0.552, meaning that sports extracurricular activities contributed 55.2% to the variation in students’ social skills. These findings indicate that sports extracurricular activities have a significant effect on improving elementary school students’ social skills. Therefore, optimizing sports extracurricular programs is important to support students’ social development at the elementary education level. Keywords: Sports Extracurricular Activities, Social Skills, Elementary School Students